Combating Diabetes in the Digital Era: Smart Strategies for Schools and Campuses for Generation Z and Alpha - Algifnita, Avina Oktaviani (BKM Public Health and Community Medicine, 2024)
Purpose: Diabetes Mellitus (DM) is a non-communicable disease with a rising global prevalence, including in Indonesia. This issue is especially critical among Generation Z and Generation Alpha, where early-onset diabetes is increasingly common. Factors such as sedentary lifestyles, unhealthy eating habits, and physical inactivity, exacerbated by technological advancements, contribute to this condition. The research gap lies in the lack of integrated and innovative approaches utilizing digital technology for diabetes prevention and management among youth in educational settings. This study aims to identify effective strategies applicable in Indonesian educational institutions to prevent diabetes among young people, drawing on successful initiatives from other countries and Mintzberg's organizational theory. Methods: This study employs a descriptive qualitative approach with case studies conducted in several schools and universities in Indonesia. Data were collected through in-depth interviews with stakeholders, participatory observation, and document analysis. The intervention strategies included developing health curricula, using mobile applications for health monitoring, providing healthy food in cafeterias, and integrating game-based physical activities (gamification). Results: The findings indicate that implementing technology-based health programs in schools and campuses can enhance students' awareness and knowledge about diabetes. Mobile health monitoring applications proved effective in tracking students' nutritional intake and physical activity. These programs also successfully increased student participation in physical activities and reduced the consumption of unhealthy foods in school cafeterias. Conclusion: Collaboration between schools, families, and communities is crucial in creating environments that support healthy lifestyles. Mintzberg's organizational theory coordinated these efforts, ensuring that all organizational components contribute to the same goals. Integrating digital technology is key to the success of these programs, but continuous innovation and adaptation are needed to sustain and adjust to the evolving habits of young generations.